Evaluating and Prioritizing the Sustainable Supply Chain Management Practices in Food Industry - Abdulqader Mansoor , Shaymaa; Yarub Maan, Harith (Journal of Economics and Administrative Sciences, 2024)
The companies are now aiming to integrate the concept of Sustainability Supply Chain Management (SSCM) into their work to improve operational and financial performance. The current study seeks to present and define the concept of the Supply Chain (SC) importance. The problem of this research it’s to determine the importance of sustainability criteria is that most companies face. A fuzzy Analytic Hierarch Process (FAHP)was used to find the relative importance of the main and sub-criteria for sustainability by establishing a program on Microsoft office Excel (MSEXCEL) to find the results and determine the importance of the main and sub-criteria based on the binary comparison list that was done by the five experts in The General Company for Food Products and Al-Mamoun Factory affiliated to the Ministry of Industry and Minerals in Iraq. The main objective of this study is to arrange the importance of the main criteria the economic, environmental, and social, thirteen sub-criteria distributed main criteria. The study concluded that the economic criterion came at (73%), followed by the environmental criterion at (16.2%), and the social criterion in third place at (10.8%), and this shows the extent of priority followed by the company in economic matters. In addition, the sub-criterion net profit was (29%), and interest in purchasing friendly materials at (8%) was in the environmental dimension, while the sub-criterion of employee satisfaction received (4%) from the criteria of the social dimension which helps the decision-maker to take the appropriate decision and improve the development of sustainable supply chains and their applicability.